Analysis of Media Expression in "Fat Cat Incident" - Ni, Jiacheng (International Journal of Social Sciences and Public Administration, 2025)
This study aims to deeply explore the media expression of the "fat cat incident" that has aroused wide concern in Chinese society in recent years. Through the analysis of mainstream media and social media coverage, this study reveals the angles, strategies and changes in public sentiment of media coverage. The research methods include text analysis and social network analysis, and the results show how the media selectively report and express events, and how these phenomena affect social opinion and public psychology.